Application of particle swarm optimization to robotic drill route optimization [electronic resource] - Asrul Adam, 1985- (2009)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2009